Les Pentecôtismes à l'assaut de la sorcellerie familiale au Cameroun - Batibonak, Sariette (Anthropologica, 2018)
According to African Pentecostals, evil forces originate primarily from the family. The familial circle in Cameroon is considered a source of danger as well as a formative influence on the individual. It is, therefore, an ambivalent matrix of both trust and suspicion. The pastors, either by force or by manipulation, take control of the individual in order to protect them from bewitchment by their family. After taking away the believer from their “evil family”, the Pentecostalists take the opportunity to fill the space by placing them into a “spiritual family.” The church becomes a new familial space for the “disparentalized” believer. This violence is expressed through speech and rituals that sometimes spill over into the public sphere.